A novel multifunctional carbon aerogel-coated platform for osteosarcoma therapy and enhanced bone regeneration. Issue 3 (29th November 2019) - Dong, Shaojie; Zhang, Ya-nan; Wan, Jianyu; Cui, Rongrong; Yu, Xingge; Zhao, Guohua; Lin, Kaili
Abstract : The implantation of multifunctional carbon aerogel (CA)-coated β-TCP scaffolds for synchronously improving the photothermal ablation and enhanced bone regeneration of osteosarcoma. Abstract : Nowadays, groundbreaking strategies are urgently needed to address drug resistance, osteolysis, bone defects and other predicaments impeding the therapeutic efficacy of osteosarcoma. Among them, photothermal therapy (PTT), using systematically administrated nanoagents, exhibits attractive therapeutic efficacy, yet is powerless in bone defect regeneration. Herein, a novel multifunctional beta-tricalcium phosphate (β-Ca3 (PO4 )2, β-TCP) bioceramic platform-coated with carbon aerogel (CA), which was initially developed for tumor therapy, was fabricated. On account of the desirable photothermal capabilities of CA, sufficient hyperthermia is generated under the irradiation of an 808 nm laser to achieve a thorough ablation of osteosarcoma tumors. Furthermore, CA-coated surfaces provide extra roughness and a higher specific surface area, which promoted the protein recruitment ability and osteogenesis via a fibronectin (FN)-mediated signaling pathway. The photothermal therapeutic efficacy and osteogenesis capability of CA-coated β-TCP-C suggests a novel approach for the treatment of osteosarcoma and provides provoking inspiration for the prospective bio-application of CA.